Phylogenetics and evolution of wheat streak mosaic virus: Its global origin and the source of the Australian epidemic. (23rd July 2022) - Jones, Roger A. C.; Vazquez‐Iglesias, Ines; Hajizadeh, Mohammad; McGreig, Samuel; Fox, Adrian; Gibbs, Adrian J.
Abstract: Wheat streak mosaic tritimovirus (WSMV) seriously damages wheat worldwide. We report analyses of new complete ORF (CO) sequences from seven Australian isolates with 56 COs and 128 coat protein (CP) genes sequenced previously. Eleven CO and three CP sequences were recombinants so were removed from our analyses. Patristic distances of maximum‐likelihood phylogenies of nonrecombinant (n‐rec) CO sequences and their CP sequences were closely correlated ( R = 0.994, p ≤ 0.00001). The phylogeny of all 188 n‐rec CP genes had four well‐supported phylogroups (I–IV): phylogroup I (one Mexican sequence), phylogroup II (six Iranian sequences), phylogroup III (48 sequences) and phylogroup IV (133 sequences), each with basal Iranian sequences and either mostly European (phylogroup III) or mostly American (phylogroup IV) terminal sequences. Australian and South American sequences formed a phylogroup IV subcluster within a Pacific Northwest USA cluster. Unlike the Iranian, South American and European populations, the North American and Australian populations demonstrated recent population imbalance. Sample collection dates of 40 CO sequences are known, allowing WSMV phylogeny dating by RTDT methodology. The most recent WSMV ancestor was dated at 1456 CE, and the Australian cluster at 1998.7 CE, only 2–3 years before WSMV was first reported. Tritimoviruses originated in central Eurasia, WSMV first entering wheat in its Middle East domestication centre and one basal lineage being taken to Mexico after the Spanish conquest, whereas the other most basal lineage spread throughout Iran, before spreading to other world regions. Probable future spread to other world regions of additional WSMV phylogroups, and of interphylogroup recombinants, constitutes a biosecurity concern. Abstract : Our analyses of new Australian and previously obtained sequences from other continents provide important information about the world wheat streak mosaic virus population, its global origin and the source of the Australian epidemic.